Environmental considerations of low-temperature drilling fluids. Issue 65 (2014) - Talalay, Pavel; Hu, Zhengyi; Xu, Huiwen; Yu, Dahui; Han, Lili; Han, Junjie; Wang, Lili
Abstract: The introduction of low-temperature fluid into boreholes drilled in ice sheets helps to remove drilling cuttings and to prevent borehole closure through visco-plastic deformation. Only special fluids, or mixtures of fluids, can satisfy the very strict criteria for deep drilling in cold ice. The effects of drilling fluid on the natural environment are analyzed from the following points of view: (1) occupational safety and health; (2) ozone depletion and global warming; (3) chemical pollution; and (4) biological pollution. Traditional low-temperature drilling fluids (kerosene-based fluids with density additives, ethanol and n -butyl acetate) cannot be qualified as intelligent choices from the safety, environmental and technological standpoints. This paper introduces a new type of low-temperature drilling fluid composed of synthetic ESTISOL TM esters, which are non-hazardous substances. ESTISOL TM 140 mixtures with ESTISOL TM 165 or ESTISOL TM F2887 have an acceptable density and viscosity at low temperature. To avoid the potential for biological contamination of the subglacial environment, the borehole drilling fluid should be treated carefully on the surface.